Crook County: racism and injustice in America's largest criminal court - Van Cleve, Nicole Gonzalez (Stanford Law Books, 2016)
Introduction : opening the courthouse doors -- Separate and unequal justice -- Of monsters and mopes : racial and criminal "immorality" -- Race in everyday legal practices -- There are no racists here : prosecutors in the criminal courts -- Rethinking Gideon's army : defense attorneys in the criminal courts -- Conclusion : racialized punishment in the courts